Penyuluhan bagi Masyarakat Peduli Sampah Polimer Termoplastik Kelurahan Rampal Celaket Kecamatan Klojen Kota Malang - Djoko Andrijono; Sufiyanto Sufiyanto (University of Merdeka Malang, 2021)
The workshop delivered to the anti-waste activists in Kelurahan Rampal Celaket, Kecamatan Klojen, Malang, is a community service program initiated by the Mechanical Engineering Department, Faculty of Engineering University of Merdeka Malang in collaboration with the Research and Community Service of IKIP Budi Utomo Malang. Plastic products caused environmental issues due to its slow decomposition rate by microorganisms, especially after being disregarded or buried in the ground. Even though the movement to reduce the use of plastic has been widely promoted, Indonesians in general do not have enough understanding of the environmental problems caused by plastic waste. In addition, the public also lacks the understanding of several other matters, including a) the properties of thermoplastic and thermosetting polymers, b) the alternative ways to reuse plastic waste as handicrafts or plastic pellets as secondary materials for plastic products. The results of preliminary observation indicated that the community need a workshop program on plastic waste management, types of recyclable plastic, and the impact of reusing plastic waste through lecture and discussion methods. This counseling reveals that a workshop program with lecture and discussion methods could increase public knowledge and awareness on plastic waste processing.DOI: https://doi.org/10.26905/abdimas.v6i2.5136